Evaluation of legal periodical collections of selected law school libraries in Metro Manila - Echiverri, Lilia Fonbuena 1951-
The general evaluation of the legal periodical collection of UPCL is rated outstanding (4.12 - 4.21) in supporting the law school program and research needs of students and faculty. The ADMUSL rated their overall program very sufficient (3.12 - 3.85). SBCLL legal periodical collection all sufficient (2.19 - 2.54) in supporting the overall programs and objectives of the college, adequacy in supporting the professional program and research needs. USTFCL also rated their law library as satisfactory (2.37 - 2.54)